Jahresgaben 1996. : Neuer Aachener Kunstverein. - NAK (Neuer Aachener Kunstverein), Aachen (Aachen : Neuer Aachener Kunstverein, 1996)
Bandau, Joachim ; Bardenheuer, Herbert ; Borchardt, Albert ; Grunschel, Norbert ; Huber, Thomas ; Jetelova, Magdalena ; Kessl, Ulrike ; Kippenberger, Martin ; Kuball, Mischa ; Linssen, Jupp ; Nestler, Wolfgang ; Nestler, Hartmut ; Ritzerfeld, Hartmut ; Schütte, Thomas ; Streuli, Beat ; Weber, Heike
Biografie
boek